Mix Design-Driven Control of Carbonation and Hydration in CO2-Mixed Cement Pastes: Effects of Water, Slag, and Surfactant - Jingliang Xia; Chunjin Li; Haoyuan Ma; Qiang Ren (Buildings)
This study systematically investigates the influence of mix proportion on and the early-age properties and CO2 uptake of CO2-mixed cement paste, focusing on variations in the water-to-binder (w/b) ratio, slag content, and air-entraining agent (AEA) dosage. Mineralogical characteristics were analyzed using X-ray diffraction (XRD) and thermogravimetric analysis (TGA), while pore structures were assessed via nitrogen adsorption. CO2 uptake was quantified immediately after mixing. Results indicate that a low w/b ratio limits CO2 dissolution and transport, favors hydration over carbonation, and leads to a coarser pore structure. At moderate w/b ratios, excess free water facilitates concurrent carbonation and hydration; however, thinner water films ultimately hinder CaCO3 precipitation and C-S-H nucleation. Slag contents up to 30% slightly suppress early carbonation and hydration, while higher dosages significantly delay both reactions and increase capillary porosity. An increasing AEA dosage stabilizes CO2 bubbles, suppressing immediate CO2 dissolution and reducing the early formation of carbonation and hydration products; excessive AEAs promotes bubble coalescence and results in an interconnected pore network. An optimized mix design, moderate water content, slag below 30%, and limited AEA dosage enhance the synergy between carbonation and hydration, improving early pore refinement and reaction kinetics.